Theoretical Approach to the Performance Analysis of a Low-Specific Speed Pump as Turbine Based on Hydraulic Losses - Nguyen, Thi Nho; Truong, Viet Anh (Old Journal, 2020)
This paper focuses on building a theoretical method, based on the calculation of hydraulic losses to predict the energy performance of a Low-specific speed Pump as Turbine (PaT) quickly and accurately that supported for the PaT’s impeller design. The Euler equation is built with the analysis of hydraulic loss calculation and flow phenomena passing on the machine. The trust of this approach is validated by comparing with the available experimental data. The results show that the theoretical energy curves of the PaT are in a good agreement with the tendency of the experimental results in both pump and turbine modes in vicinity of design point. Thereby, we estimated the head loss distributions in the flow system of PaT, including: the total of the head loss, the impeller loss, the disk friction and spiral casing losses. From these results, to improve and harmonize the efficiency of reversible impeller in both pump and turbine modes, the designer is recommended to decrease the diameter D₂ and increase the impeller widths b₁, b₂ for improvement.